Induction and suppression of allergic diarrhea and systemic anaphylaxis in a mouse model of food allergy - Kucuk, Zeynep Yesim (2012)
BACKGROUND: The clinical manifestations of food allergy include diarrhea and systemic anaphylaxis (shock), which can occur together or by themselves in different individuals. Although ingested food antigens need to be absorbed to induce shock, it is not known whether they need to be absorbed to induce diarrhea. OBJECTIVE: Identify mechanisms that determine whether food allergy induces diarrhea versus shock and determine whether diarrhea requires absorption of ingested antigens. Methods: These issues were studied in mice in active, passive and hybrid immunization models. The active model was used to determine the allergic diarrhea susceptibility of J chain- and pIgR-deficient mice, which are unable to secrete IgA. The hybrid model was used to determine whether intravenously administered antigen-specific IgG antibody, which is not secreted into the gut, can protect against allergic diarrhea as well as shock. RESULTS: Shock, but not diarrhea was induced in naïve mice by intravenous IgE anti-TNP antibody, followed by oral TNP-bovine serum albumin, whereas both were induced in mice presensitized with intraperitoneal ovalbumin/alum plus oral ovalbumin. More TNP-bovine serum albumin was required to induce shock than diarrhea in presensitized mice and intravenous IgG anti-TNP antibody, which is not secreted into the gut, protected these mice against both diarrhea and shock. Consistent with this, OVA-immunized J chain- and pIgR-deficient mice, which have high serum IgA but little intestinal IgA, resisted diarrhea induction. CONCLUSION: Intestinal immunity and oral Ag dose determine whether diarrhea and/or systemic anaphylaxis are induced and ingested Ag must be absorbed to induce either response.